Penamaan Usaha Mikro di Wilayah Perbatasan Jambi – Riau: Kajian Lanskap Linguistik - Teresia , Meisinta Ayu; Kusmana, Ade; Izar, Julisah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This study aims to see the information function and symbolic function of naming micro-businesses in the Jambi-Riau Border area with a Linguistic Landscape Study. The research method is descriptive with a qualitative approach. After that, the data obtained were in the form of interview results and visual portraits of business nameplates located in the Jambi-Riau Border Area, precisely in Suban Village and Sungai Penoban Village, Batang Asam District. Data was obtained from thirty-two informants. The techniques used to obtain data were Observation, Interviews and Visual Portraits. Then the data obtained were analyzed using descriptive analysis techniques. Based on research that has been conducted in the Jambi-Riau border area, monolingual, bilingual, and multilingual forms were found in naming business names. Monolingual and bilingual forms dominate business names in the Jambi-Riau border area. Based on the information function, it shows the use of regional languages, foreign languages, and personal power in naming business names in the Jambi-Riau border area. Abstrak Peneltian ini bertujuan untuk melihat fungsi informasi dan fungsi simbolik penamaan usaha mikro di wilayah Perbatasan Jambi – Riau dengan Kajian Lanskap Linguistik. Metode penelitian bersifat deskriptif dengan pendekatan kualitatif. Setelah itu data yang diperoleh berupa hasil wawancara dan potret visual papan nama usaha yang berada di Wilayah Perbatasan Jambi – Riau tepatnya di Desa Suban dan Desa Sungai Penoban Kecamatan Batang Asam. Data diperoleh dari tiga puluh dua Informan. Adapun Teknik yang digunakan untuk memperoleh data yaitu Observasi, Wawancara dan Potret Visual. Kemudian data yang diperoleh dianalisis menggunakan teknik analisis deskriptif. Berdasarkan penelitian yang telah dilakukan di wilayah perbatasan Jambi – Riau ditemukan bentuk monolingual, bilingual, dan multilingual dalam penamaan nama usaha. Bentuk monolingual dan bilingual mendominasi penamaan usaha di wilayah perbatasan Jambi-Riau. Berdasarkan fungsi informasi, menunjukan adanya penggunaan Bahasa daerah, Bahasa asing, dan kekuasaan pribadi dalam penamaan nama usaha di wilayah perbatasan Jambi Riau.